Clinical significance of an ultrafast alkaline phosphatase isoenzyme. Issue 12 (December 1979) - Koett, J; Howell, J; Wolf, P L
Abstract : We have studied five patients who have exhibited an unusual alkaline phosphatase isoenzyme (ALP EC 3.1.3.1) migrating in an ultrafast position electrophoretically on cellulose acetate. This ALP isoenzyme has been identified in patients with benign and malignant liver diseases. In addition, a number of these patients exhibited a regular ALP liver isoenzyme and a fast (preliver) ALP isoenzyme in conjunction with the ultrafast ALP liver isoenzyme.